G196(P) Making or Breaking Trainees: Experience from a Network Neonatal Intensive Care Unit. (7th April 2014) - Bell, C; Lilley, J; Richardson, G
Abstract : Aims: This study was designed to assess intubation practice in a Network NICU. Methods: This was a prospective audit on all intubations occurring in a Network NICU for a 100 day period commencing July 31st 2013. Data was collected by means of a questionnaire completed immediately post procedure by the practitioner involved. Baseline data on both the infant and practitioner were collected along with technical details about the procedure. Results: During the 100 day period of the audit there were 63 intubations, consisting of intubation or re-intubation of 27 infants. Level 1 trainees performed 30% of the intubations during this period. In addition 12 intubations on infants less than 28 weeks were performed by level 1 trainees. On average there were 1.29 attempts for each intubation by Level 1 trainees. In the event of unsuccessful attempt by a level 1 trainee all infants were subsequently intubated by the Level 3 trainee, ANNP or Consultant who was providing supervision. Conclusion: Our unit has fewer level 3 trainees as a result of their rotation through the local tertiary hospital. This has necessitated employing ST3 trainees on the Tier 2 rota. Intelligent Rostering has been utilised to ensure that these trainees are adequately supported in this role while gaining experience in working in a network NICU. All trainees who have not worked at middle grade level in a Network NICU are paired with ANNPs on the Tier 1 rota to provide them with additional support. Originally this audit was designed to look at intubation practice on the neonatal unit, specifically procedural elements such as premedication. However as results have been analysed a striking feature has been the number of intubations performed by level 1 trainees. This included a high proportion of infants born extremely preterm, a group of infants who are potentially the most challenging. The results would seem to suggest the unit has developed a multidisciplinary approach to supporting level 1 trainees in achieving these and other competencies.